Inglorious empire : what the British did to India - Tharoor, Shashi 1956- (London : Penguin, 2017)
Inglorious Empire' tells the real story of the British in India from the arrival of the East India Company to the end of the Raj, revealing how Britain's rise was built upon its plunder of India. In the eighteenth century, India's share of the world economy was as large as Europe's. By 1947, after two centuries of British rule, it had decreased six-fold. Beyond conquest and deception, the Empire blew rebels from cannon, massacred unarmed protesters, entrenched institutionalised racism, and caused millions to die from starvation. British imperialism justified itself as enlightened despotism for the benefit of the governed, but Shashi Tharoor takes on and demolishes this position, demonstrating how every supposed imperial "gift" - from the railways to the rule of law -was designed in Britain's interests alone. He goes on to show how Britain's Industrial Revolution was founded on India's deindustrialisation, and the destruction of its textile industry.
Chronology -- Acknowledgements -- Preface -- The Looting of India -- Did the British Give India Political Unity? -- Democracy, the Press, the Parliamentary System and the Rule of Law -- Divide Et Impera -- The Myth of the Enlightened Despotism -- The Remaining Case for Empire -- The (Im)Balance Sheet: A Coda -- The Messy Afterlife of Colonialism -- Notes and References -- Bibliography -- Index.
Includes bibliographical references (pages 251-288) and index.
AAL
Keywords: Imperialism; India -- History -- British occupation, 1765-1947; Great Britain -- Foreign relations -- India; India -- Foreign relations -- Great Britain